Directory of world cinema. American Hollywood. 2 - Geraghty, Lincoln, 1977- (Bristol : Intellect, 2015)
Hollywood continues to reign supreme; from award-winning dramas to multimillion-dollar, special effects-laden blockbusters, Tinseltown produces the films that audiences around the world go to the cinema to see. While the film industry has changed dramatically over the years-stars have come and gone, studios have risen and fallen, new technologies have emerged to challenge directors and entice audiences-Hollywood remains the center of global media entertainment. This second volume of 'Directory of World Cinema: American Hollywood' builds on its predecessor by exploring how the industry has evolved and expanded throughout its history. With new essays that discuss the importance of genre, adaptation, locations, and technology in the production of film, this collection explores how Hollywood has looked to create, innovate, borrow, and adapt new methods of filmmaking to capture the audience's imagination.
Adaptation: Hollywood in the twenty-first century -- Locating Hollywood -- Hollywood and technology -- Industry spotlight: The Avengers/Marvel's Avengers assemble -- Directors. James Cameron -- Frank Capra -- Nora Ephron -- Alfred Hitchcock -- Christopher Nolan -- Awards -- Marketing -- Sound & music -- Special effects & CGI -- TV to film -- Remakes -- Teen films -- Superhero and comic book films -- Computer game adaptations -- Christmas and the holidays -- Thrillers -- The sport film.
Includes bibliographical references (pages 284-293).
Print version record.
JSTOR
Keywords: Motion pictures -- United States -- History; Motion pictures -- United States -- Reviews; Motion picture industry -- California -- Los Angeles; Motion picture industry -- California -- Los Angeles -- History; Cinéma -- États-Unis -- Histoire; Cinéma -- Industrie -- Californie -- Los Angeles; Cinéma -- Industrie -- Californie -- Los Angeles -- Histoire; PERFORMING ARTS / Film & Video / Reference; Motion picture industry; Motion pictures; California -- Los Angeles; United States; Electronic books; History; Reviews